Clinical Application of Nerve Intervention in Cerebrovascular Diseases - Zhao, Xin (Clinical Application of Nerve Intervention in Cerebrovascular Diseases, 2021)
The author focuses on the hot spots and frontier contents of neurointerventional therapy for cerebrovascular diseases, and discuss the basic characteristics, treatment decision and choice, interventional surgical techniques, prevention and treatment of complications and other aspects of typical cerebrovascular diseases. This book describes the detailed operation analysis and the targeted comment to 11 typical cases, explains the possible solution to the problem in the clinical treatment process. The content is practical, the theory is combined with the practice, the pictures are illustrated, and it can be an important reference book for neurointerventional physicians.